2009
DOI: 10.1088/1475-7516/2009/12/006
|View full text |Cite
|
Sign up to set email alerts
|

Quantum tunneling in flux compactifications

Abstract: We identify instantons representing vacuum decay in a 6-dimensional toy model for string theory flux compactifications, with the two extra dimensions compactified on a sphere. We evaluate the instanton action for tunneling between different flux vacua, as well as for the decompactification decay channel. The bubbles resulting from flux tunneling have an unusual structure. They are bounded by two-dimensional branes, which are localized in the extra dimensions. This has important implications for bubble collisio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(130 citation statements)
references
References 48 publications
2
127
0
1
Order By: Relevance
“…Therefore the 'nothing' inside the bubble of nothing should be understood as the limit of anti-de Sitter space as the curvature length approaches zero. 9 We then applied this understanding of nothing to the question of the quantum creation of a universe using a Hawking-Turok instanton, which we embedded within the Coleman-De Luccia formalism. We argued that, since up-tunneling from anti-de Sitter space is forbidden, it is impossible to start with nothing and create a universe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the 'nothing' inside the bubble of nothing should be understood as the limit of anti-de Sitter space as the curvature length approaches zero. 9 We then applied this understanding of nothing to the question of the quantum creation of a universe using a Hawking-Turok instanton, which we embedded within the Coleman-De Luccia formalism. We argued that, since up-tunneling from anti-de Sitter space is forbidden, it is impossible to start with nothing and create a universe.…”
Section: Discussionmentioning
confidence: 99%
“…By examining solutions close to the bubble of nothing, we will gain insight into the nature of nothing. Let's begin by studying this approach to the bubble of nothing in the simplest possible model with perturbatively stabilized extra dimensions, the 6D Einstein-Maxwell theory [8,9], a model whose tunneling instantons we constructed explicitly in [10].…”
Section: Bubbles Of Nothing In Stabilized Extra Dimensions: a Simple mentioning
confidence: 99%
“…In the context of a scalar field, such a cascade of classical transitions seems to rely on the existence of roughly evenly spaced vacua in the potential landscape. Interestingly, in [33] it is shown that in a model with multiple vacua constructed from extra dimensions and fluxes, a classical transition is the most natural result, as shown in Figure 14. In these models, the multiple classical transition structure in Figure 13 should be taken seriously.…”
Section: E Multiple Collisionsmentioning
confidence: 98%
“…In this article, we study a simple model (Halliwell [5] and Blanco-Pillado, Schwartz-Perlov, and Vilenkin [6]), which we will call the HBSV model. Let us begin with the six-dimensional action:…”
Section: Flux Compactification In String Theorymentioning
confidence: 99%